1996
DOI: 10.1016/0735-1097(96)82380-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vascular reactivity in insulin-dependent diabetes mellitus is related to disease duration and low density lipoprotein cholesterol levels

Abstract: Vascular reactivity is impaired in the systemic arteries of asymptomatic young adults with insulin-dependent diabetes and may represent early large-vessel disease. The degree of impairment is related to the duration of diabetes, and these patients appear particularly vulnerable to damage from LDL cholesterol, even at levels considered acceptable in nondiabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
5
11

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(198 citation statements)
references
References 35 publications
8
174
5
11
Order By: Relevance
“…Sample size calculations were performed based on the FMD component of the study. In previous studies of healthy subjects, reported mean FMD values have ranged from 106% to 112% (SD 3-6.5%), while in subjects with vascular risk factors such as cigarette smoking, hypertension, or hypercholesterolemia, mean FMD ranged from 100% to 106.5% (20,36,37). For the purpose of sample size calculations we estimated a mean Ϯ SD FMD of 108 Ϯ 4% in our healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculations were performed based on the FMD component of the study. In previous studies of healthy subjects, reported mean FMD values have ranged from 106% to 112% (SD 3-6.5%), while in subjects with vascular risk factors such as cigarette smoking, hypertension, or hypercholesterolemia, mean FMD ranged from 100% to 106.5% (20,36,37). For the purpose of sample size calculations we estimated a mean Ϯ SD FMD of 108 Ϯ 4% in our healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…Endothelium-dependent vasodilation impaired by dietary glucose ingestion seemed to be restored by consumption of antioxidant vitamins (Levine et al, 1996;Title et al, 2000;Skyrme-Jones et al, 2000). Diabetic patients (type 1 and 2) tend to be more prone to endothelial dysfunction (eg decreased endothelium-dependent vasodilation) and to have higher levels of oxidative stress than healthy populations (Clarkson et al, 1996;Williams et al, 1996;Akkus et al, 1996;Santini et al, 1997;Ceriello et al, 1998b) and in healthy individuals postprandial hyperglycemia appears to result in increased oxidative stress (Koska et al, 1997;Ceriello et al, 1998a;Kawano et al, 1999).…”
Section: The Glycemic Index In Coronary Heart Diseasementioning
confidence: 98%
“…A variety of other perturbations have been reported in the coagulation systems of diabetic patients that might affect platelet function, including larger platelets, 8 greater expression of P-selectin, 14 higher platelet surface density of GP IIb/IIIa, 8,9 altered thromboxane metabolism, 15 and higher levels of circulating fibrinogen, 10 vitronectin, 16,17 and thrombin-antithrombin III complexes, 18 as well as more extensive endothelial dysfunction. 19,20 Diabetic patients also have higher mortality in the acute coronary syndromes 21 and in general have more extensive coronary artery disease than do nondiabetics. These differences may be reflected in the makeup of the target coronary arterial lesions.…”
Section: Discussionmentioning
confidence: 99%